Pregnant women's decision to vaccinate against Covid-19: scope review protocol (Research, Society and Development, 2022)
Objective: to identify and map the evidence regarding the decision of pregnant women about vaccination against Covid-19 in the scientific literature. Method: Scope Review protocol conducted according to the JBI manual, using the PRISMA checklist extension in the following search bases: Medline, Web of Science and Scopus. The study will be conducted in August 2022, guided by the research question: “What are the factors that impact the acceptance or hesitation of pregnant women to be vaccinated against Covid-19?”. Rayyan software will be used to manage the collection and selection of studies published between January 2020 and May 2022. The title and abstract of all identified studies will be evaluated, based on the inclusion criteria and exclusions established, by two independent reviewers and by a third reviewer to resolve possible discrepancies. The data will be descriptively summarized. A flowchart and narrative summary will accompany the results and describe how they relate to the objective and issue of the review. Record of review in the Open Science Framework: DOI: 10.17605/OSF.IO/NFUDT. The information from the review instrumented from this protocol will be useful to observe the factors that influence the decision of pregnant women in relation to vaccination against Covid-19 and to support public policies in force in the country; which, in turn, can contribute to expanding vaccination coverage and reducing maternal morbidity and mortality from Covid-19.